2017
DOI: 10.1089/ars.2016.6662
|View full text |Cite
|
Sign up to set email alerts
|

Loss of NAD-Dependent Protein Deacetylase Sirtuin-2 Alters Mitochondrial Protein Acetylation and Dysregulates Mitophagy

Abstract: Together, these findings support that SIRT2 functions as a mitochondrial sirtuin, as well as a regulator of autophagy/mitophagy to maintain mitochondrial biology, thus facilitating cell survival. Antioxid. Redox Signal. 26, 849-863.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
92
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(98 citation statements)
references
References 47 publications
6
92
0
Order By: Relevance
“…Conversely, there is a reduction of PINK1 in CR mice, indicating that CR may attenuate mitochondrial damage. CR‐mediated autophagy that is dependent on SIRT1 increases mitophagy, whereas a loss of SIRT2 function leads to a dysregulation in mitophagy . AMPK is also implicated in mitophagy via the activation of Ulk1 …”
Section: Calorie Restriction Regulates Brain Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, there is a reduction of PINK1 in CR mice, indicating that CR may attenuate mitochondrial damage. CR‐mediated autophagy that is dependent on SIRT1 increases mitophagy, whereas a loss of SIRT2 function leads to a dysregulation in mitophagy . AMPK is also implicated in mitophagy via the activation of Ulk1 …”
Section: Calorie Restriction Regulates Brain Functionmentioning
confidence: 99%
“…CR-mediated autophagy that is dependent on SIRT1 increases mitophagy, 87 whereas a loss of SIRT2 function leads to a dysregulation in mitophagy. 88 AMPK is also implicated in mitophagy via the activation of Ulk1. 34 CR decreases levels of ROS in the rat brain 89 and reduces the amount of oxidative damage to mitochondrial DNA in liver.…”
Section: Cr and Mitochondrial Healthmentioning
confidence: 99%
“…However, multiple other signal transduction pathways are also involved in autophagy, including forkhead box protein O1, p38 mitogen-activated protein kinase, and Akt 2 (also known as RAC-β serine/threonine protein kinase) 221 . Importantly, autophagy and mitophagy are regulated by sirtuins, a family of NAD-dependent protein deacetylases 222224 . Numerous studies have revealed a role for microRNAs (miRNAs) in the regulation of cardiac autophagy; some of these miRNAs are in the circulation or are delivered via exosomes 225240 .…”
Section: Autophagy As a New Therapeutic Targetmentioning
confidence: 99%
“…Therefore, deacetylation of specific substrates, (e.g., histones and transcriptional factors), occurs via the cofactor NAD 1 (Liu et al, 2015). Sirtuins also regulate fundamental biological processes, inclusive of glucose homeostasis, bioenergetic transduction, cell differentiation, and apoptosis (Liu et al, 2016a).…”
Section: Gsh and Disruptions Of Redox Homeostasismentioning
confidence: 99%
“…The presence of free cytosolic DNA leads to AIM2 inflammasome activation, and it has recently been demonstrated that mitochondria are a major source of DAMPs, which trigger neuroinflammatory responses resulting in apoptosis, pyroptosis, and autophagy (Liu et al, 2016a).…”
Section: Neuroinflammationmentioning
confidence: 99%